INTEGRASI TEKNOLOGI ARTIFICIAL INTELLIGENCE (AI) TERHADAP KEMAMPUAN LITERASI SAINS SISWA SEKOLAH DASAR: NARRATIVE LITERATURE REVIEW - Izza, Nur; Putri Rusnadi, Riska; Yusuf, Narda; Ibrahim; Rahmawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of Artificial Intelligence (AI) technology has had a significant impact on the world of education, particularly in Natural Science learning in elementary schools. This study aims to examine the integration of AI technology on the scientific literacy skills of elementary school students through a narrative literature review approach. The research method involves a literature search on the Google Scholar and Garuda Kemdiktisaintek databases, covering 25 scientific articles published between 2022 and 2026. All articles were analyzed descriptively and narratively through identification, thematic clustering, and synthesis of findings. The study results show that AI integration in various forms such as adaptive learning systems, chatbots, and virtual laboratories has proven effective in enhancing conceptual understanding, critical thinking skills, and student learning motivation. AI functions as a creative facilitator that strengthens the teacher's role and achieves optimal results when combined with active pedagogical approaches such as STEM and Problem-Based Learning (PBL). However, AI implementation still faces systemic challenges, including infrastructure limitations, low teacher digital literacy (TPACK), and the risk of technology dependency. This study concludes that while AI has substantive potential to improve science literacy, its success requires an ecosystemic approach involving infrastructure readiness, educator competency development, and carefully planned pedagogical design.